Determinants Budgetary Slack - Ningrum Pramudiati; Anandita Zulia Putri; Betti Prastiwi (Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to examine the determinants of budgetary slack. Budgetary slack often occurs because of pressure from superiors aimed at subordinates to make a reasonable budget. This study examines the effect of the independent variables, namely budgetary participation, information asymmetry, budget emphasis, and organizational commitment, on the dependent variable, namely budgetary slack. This study used a sample of Regional Apparatus Organizations (OPD) in Bantul Regency. The number of samples used in this study was 78 respondents using the purposive sampling method. The data analysis technique used is multiple linear regression. The study results of the study prove that the budget participation variable has a positive effect on budgetary slack with a significance of 5%. Meanwhile, the variables of information asymmetry, budget emphasis, and organizational commitment do not affect budgetary slack. Keywords: budget participation, information asymmetry, budget emphasis, organizational commitment, budgetary slack